Hyperhomocysteinemia as a potential contributor of colorectal cancer development in inflammatory bowel diseases: A review - Keshteli, Ammar Hassanzadeh (World J Gastroenterol, 2015)
Homocysteine is an amino acid generated metabolically by the S-adenosylmethionine-dependent transmethylation pathway. In addition to being a well-known independent risk factor for coronary heart disease, is also a risk factor for cancer. Patients suffering from inflammatory bowel diseases (IBD) including ulcerative colitis and Crohn’s disease are at increased risk of developing colorectal cancer in comparison to healthy individuals. Furthermore, the risk of hyperhomocysteinaemia is significantly higher in IBD patients when compared with controls. In the present article, we review the mechanisms in which hyperhomocysteinemia may contribute to increased risk of colorectal cancer in IBD patients.